A Preliminary Study on Cancer Patients’ Quality of Life during the COVID-19 Pandemic - Ririn Afrian Sulistyawati; Santoso Santoso; Lalu Muhammad Panji Azali; Galih Setia Adi (http://dharmais.co.id/, 2023)
Background: Cancer patients are 3.5 times more susceptible to COVID-19 than patients without cancer. The increasing number of COVID-19 patients is likely to impact cancer patients’ quality of life (QoL) significantly. This study aims to analyze the QoL of cancer patients during the COVID-19 pandemic. Methods: The method used is quantitative with a cross-sectional research design. In this study, 60 respondents were selected using the Consecutive Sampling Technique. The patient’s QoL was measured once by utilizing The World Health Organization Quality of Life Brief Version (WHOQOL BREF) instrument. The QoL of cancer patients was shown in mean and standard deviation, and the correlation between respondent characteristics and QoL was analyzed with Spearman.Results: The results showed that the average QoL of the respondents in the physical health was 30.36 ± 7.72, the intermediate psychological was 25.88 ± 9.14, the average social relationship was 59.90 ± 13.04, and the mean environment was 56.7 ± 10.93.Conclusions: Respondents’ low QoL during the COVID-19 pandemic for all domains. This study implies the importance of paying attention to every domain of the QoL of cancer patients, especially during the COVID-19 pandemic.